Capacity Building of Ready to serve Fish Processor in Micro Enterprises for Business Continuity in Pringsewu District - Komang Eke Suwardane; Anna Fatchiya; Basita Sugihen Ginting (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluh Pertanian Indonesia), 2019)
Fish processors in Pringsewu district are mostly engaged in micro-scale business. The problem faced by this micro-scale business is the fish processor capacity problem, such as the technical and managerial ability. This research aims to measure the processor capacity, the factors that affect the processor capacity and the effect of processor capacity on the business sustainability. This research was conducted in two fish processor centers, in Pringsewu and Pagelaran districts. Data collection was conducted in April 2018. Data were collected from all 75 fish processors. The data collected were analyzed using descriptive and inferential statistic, with Statistical Package for Social Science (SPSS) version 24 and Partial Least Square (PLS) 3 program. The results showed that processor capacity of fish in Pringsewu district was in a low category because they have not expert in technical and managerial skills yet. Three factors that affect the processor capacity is their individual characteristics, extension support, and external support. Individual characteristic factors are the level of formal and non-formal education. The extension support factors are intensity and extension methods. External support factor also of support from the government. Other results indicate that the processor capacity has a positive effect on the business sustainability. The higher the technical and managerial capacity of the processor, the business sustainability in the economic and environmental aspects will be increase.